1997
DOI: 10.1074/jbc.272.6.3527
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pyruvic Acid Methyl Ester on Rat Pancreatic Islets

Abstract: The methyl ester of pyruvic acid (methyl pyruvate) stimulated a dose-dependent increase in insulin secretion from isolated perifused rat islets. The threshold level for release was about 10 mM, and at 20 mM the addition of MP to perifused islets resulted in a large first phase of secretion followed by an insulin-secretory response that was sustained for at least 40 min. When compared to the effects of 20 mM glucose, peak firstphase release rates in response to 20 mM methyl pyruvate were comparable, but the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…We hypothesize that this difference is due to low transport capacity for pyruvate in native β cells. The fact that a membrane-permeable analogue of pyruvate, methylpyruvate, is a potent secretagogue in isolated islets supports this idea (12,13,26). To test this hypothesis, we infected isolated rat islets with AdCAMCT-1 to increase the monocarboxylate transport activity in the β cell.…”
Section: Effects Of Ldh-a And/or Mct-1 Overexpression On Insulin Secrsupporting
confidence: 59%
See 2 more Smart Citations
“…We hypothesize that this difference is due to low transport capacity for pyruvate in native β cells. The fact that a membrane-permeable analogue of pyruvate, methylpyruvate, is a potent secretagogue in isolated islets supports this idea (12,13,26). To test this hypothesis, we infected isolated rat islets with AdCAMCT-1 to increase the monocarboxylate transport activity in the β cell.…”
Section: Effects Of Ldh-a And/or Mct-1 Overexpression On Insulin Secrsupporting
confidence: 59%
“…Pyruvate and lactate have been reported to be metabolized, but do not cause insulin secretion in pancreatic islets (11)(12)(13)(14)(15). Hence, the oxidation rate of 30 mM [1-14 C]pyruvate was found to be as high as that of 16.7 mM [U-14 C]glucose without any increase in insulin secretion (11).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The so-called "pyruvate paradox" is one such example because the mitochondrial fuel pyruvate is readily oxidized in islet preparations but does not elicit insulin secretion (20,21). In contrast, glyceraldehyde, which functions both as a cytosolic and mitochondrial fuel, is a potent secretagogue (22)(23)(24).…”
mentioning
confidence: 99%
“…A fundamental question underlying glucose-induced insulin secretion relates to the source of the increased [ATP] in response to glucose uptake. Some investigators have argued that glycolytic, but not Krebs cycle metabolism of glucose is critically involved in this signaling process [24,25]. Studies have demonstrated that inhibitors of glycolysis suppress glucose-stimulated insulin secretion, whereas methyl pyruvate can generate a normal secretory response.…”
Section: Glucose-induced Insulin Secretionmentioning
confidence: 99%